The Resources of Others: Dutch Exploitation of European Expansion and Empires, 1570-1800 - Antunes, Cátia (2018)
Historiography pertaining to the study of European colonial empires can generally be defined in two different strands: on the one hand, the nationally geared scholarship that zooms in on the development of specific ‘national’ empires and their relationships to non-European individuals, groups and polities and, on the other hand, narratives that privilege the focus on the colony and the colony’s links to the outside world. What neither of these strands does, however, is to question the role foreigners played in the capturing of resources within the logic of a foreign empire and how those resources were transferred to the places of origin of these individuals and groups. This article provides an overview of Dutch participation in the empires of others (English, French, Spanish and Portuguese) by underlining the important role that Dutch merchants, investors and labour specialists played in the exploitation of other, often competing, European empires. While some of the acquired resources remained in the host society where Dutch merchants and firms settled, some of the colonial resources and by-products were sent back to the merchants’ and firms’ places of origin, more often than not through complex transnational networks of contacts and divergent groups of interests